Finance, globalization and urban primacy - Ioannou, S; Wojcik, D (Taylor & Francis, 2021)
We use data from 131 countries in the period 2000–14 to analyze the determinants of urban primacy, calculated as the share of the city with the largest gross domestic product (GDP) in a country in the total GDP of that country. While prior research has largely neglected the role of financial factors, we demonstrate that urban primacy is related positively to the size of financial activity. In addition, currency depreciation in relation to the US dollar is related to lower urban primacy, while gross capital outflows are related to higher urban primacy. We find that trade openness—a key indicator of globalization—also coincides with higher urban primacy, but this relationship is statistically and economically less significant than that between finance and urban primacy. Among other factors, we show that urban primacy is smaller in countries with a large population, high population density, a large agricultural sector, and a federal political structure, and particularly high in countries where primate cities have seaport functions. Our main results hold in both developed and developing countries. We discuss a wide range of mechanisms through which finance can affect urban primacy, including agglomeration economies, proximity to power, access to capital, financialization, and financial instability. In short, finance has a crucial impact on the geographic distribution of economic activity.